2006
DOI: 10.1177/0095798406292470
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Context: A Study of Neighborhood Effects on Racial Socialization and Ethnic Identity Content in a Sample of African American Adolescents

Abstract: Ethnic identity is believed by some to function as a protective factor for ethnic minority youth, in particular African American youth. Although ethnic identity development is primarily the result of racial socialization practices, it may also be influenced by other contextual factors. Neighborhood factors, parent characteristics, parenting style, and bicultural competence may play pivotal roles in the ethnic identity development of African American youth. Exploratory factor analysis and path analysis were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…Scholars have specifically argued that middle to late childhood is a crucial developmental period, "particularly because it is a time when children meet different, overlapping contexts which they need to negotiate as they move into Downloaded by [Australian National University] at 10:06 04 June 2016 adolescence and adulthood" (Cooper et al, 2005, p. 11). Thus a closer, systematic look at the social contexts in which pre-adolescent language minority students live and go to school will contribute to an understanding of the forces that support developmental processes such as ethnic identity formation (Bennett, 2006;Gonzalez, 2009;Supple, Ghazarian, Frabutt, Plunkett, & Sands, 2006).…”
Section: School and Neighborhood Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have specifically argued that middle to late childhood is a crucial developmental period, "particularly because it is a time when children meet different, overlapping contexts which they need to negotiate as they move into Downloaded by [Australian National University] at 10:06 04 June 2016 adolescence and adulthood" (Cooper et al, 2005, p. 11). Thus a closer, systematic look at the social contexts in which pre-adolescent language minority students live and go to school will contribute to an understanding of the forces that support developmental processes such as ethnic identity formation (Bennett, 2006;Gonzalez, 2009;Supple, Ghazarian, Frabutt, Plunkett, & Sands, 2006).…”
Section: School and Neighborhood Contextmentioning
confidence: 99%
“…A strong ethnic identity has been found to be related to a variety of developmental and educational outcomes for minority and immigrant youth (Bennett, 2006;Phinney, 1991;Phinney & Chivara, 1992;Umana-Taylor, 2003;Zarate, Bhimji, & Reese, 2005). Despite disciplinary differences, most scholars agree that ethnic identity is a social-psychological construct that involves a feeling of belonging, intersubjectively shared by individuals in a given ethnic group (Phinney, 1990;Suárez-Orozco & Suárez-Orozco, 2004;Tajfel & Turner, 1979).…”
Section: Language and Identitymentioning
confidence: 99%
“…Some have reported that children who receive more racial socialization perform better in school or have higher cognitive scores (Bowman and Howard 1985;Caughy et al 2002aCaughy et al , 2006 although some researchers have reported no association (Phinney and Chavira 1995) or a negative association (Marshall 1995). The findings regarding the association of racial socialization practices and socioemotional outcomes such as depression or problem behaviors have been more consistent, with racial socialization negatively associated with such outcomes (Arroyo and Zigler 1995;Bennett 2006;Caughy et al 2002aCaughy et al , 2006Davis and Stevenson 2006;McHale et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…At the regional level, Thornton et al (1990) found that African Americans living in the Northeast were more likely to report engaging in racial socialization than those living in the South. Marshall (1995) reported that parents living in predominantly black neighborhoods were more likely to report engaging in racial socialization practices, and Bennett (2006) reported that racial socialization practices were negatively associated with neighborhood risky conditions. Similarly, Caughy et al (2006) found that African American parents living in predominantly white neighborhoods were less likely to convey messages regarding promotion of mistrust than African Americans living in black or racially mixed neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies do not reject the importance of social disorganization, they are far from affirming the prominence it receives within the macroeconomic thesis of neighborhood change. Massey and Denton's (1993) suggestion that segregated African Americans hold oppositional orientations toward educational opportunity alludes to the neighborhood's role in racial identity development (Bennett, 2006;Borjas, 1995;Smith, Atkins, & Connell, 2003). The ethnic/racial socialization model formalizes direct and indirect ways in which racial socialization mechanisms work.…”
Section: Social Disorganization and Violence Processesmentioning
confidence: 99%